Methane sources and sinks in karst systems: the Nerja cave and its vadose environment (Spain). - Ojeda, Lucía; Vadillo-Pérez, Iñaki; Etiope, Giuseppe; Benavente, José; Liñán-Baena, Cristina; Del Rosal Padial, Yolanda Remedios; Tapia-Paniagua, Silvana Teresa; Moriñigo-Gutiérrez, Miguel Ángel; Carrasco, Francisco (Elsevier, 2019)
Karst caves are considered a natural sink of atmospheric methane (CH4). Studies generally focus on measuring CH4 within the cave environment, and little information is available about the factors influencing CH4 abundance, such as the surrounding vadose and saturated zones of the aquifer, inputs of carbon dioxide (CO2) – a potential precursor of CH4 – and methanotrophic bacteria, which is likely the main cause of CH4 consumption. In this paper we report the first study of CH4 budget in Nerja, one of the main karst caves in Spain, based on seasonal monitoring of CH4 and CO2 concentration and stable C iso- topic ratio in the cave system, integrated with analogue data from the underlying and overlying saturated/vadose zone, and methanotrophic bacteria activity (rDNA and Polymerase Chain Reaction analyses) in cave sediments and water. The results show that the cave environment consumes, via methanotrophic activity and through c- and a–Proteobacteria, CH4 coming from both the atmosphere and the vadose/saturated zones of the aquifer, where it is produced microbially. However, vadose zone methanogenesis may seasonally exceed the methanotrophy capacity of the cave, resulting in a net CH4 increase in it. This competition process may be an important factor limiting the sink potential of karst caves.
https://openpolicyfinder.jisc.ac.uk/id/publication/7181
Keywords: Metano; Gases de efecto invernadero; Karst; Cuevas - España; Cave; Methane; Greenhouse gas; Methanotrophy; Methanogenesis; Karst